Hubungan Obesitas Remaja Dengan Gambaran Citra Tubuh Di MTSN 1 Bondowoso Desa Traktakan Kecamatan Wonosari - Lestari, Siti Rahmi; Trilianto, Arif Eko; Siddiq, Pasidi (Jurnal Keperawatan Profesional, 2021)
Obesity is a problem which is scared by all ages, including juvenile ages because it can affect the change in physical appearance.A change in physical appearance certainly can influence their body image in juvenile age. The objective of the study is correlation between juveniles obesity ang body image in student of MTsN I Bondowoso at Traktakan Village Wonosari districts.This study is kuantitatif research, the population is all of students from MTsN I BondowosoTraktakan village Wonosaridistricts.a sample 28 ( twentyeigh) people, sampling using proposive sampling, data analysis using the Spearman Rho. The score of correlation test showed from SPSS 17  that the Spearman Rho value p < 0,05 can to correlation value p = 0,040 value p = 0,040 is smaller than 0,05,and r = 0,391 which means the hypothsis is accepted.The result of this research found that there was significentcorrelation between juvenile obesity and body image in students of MTsN I Bondowoso. From the resultof this study,researchers are looking forward to a change in adolescent to diet and exercise activities that routine to maintain ideal body weight